2014
DOI: 10.3109/00207454.2014.991925
|View full text |Cite
|
Sign up to set email alerts
|

The role of biochemical risk factors in the etiology of AIS in children and adults

Abstract: Stroke is an abrupt onset of both focal and global neurological deficits secondary to a vascular event lasting more than 24 h and with a vascular background as its only cause. It can be triggered by a rupture of a blood vessel, aneurysm (hemorrhagic stroke, HS), thrombosis or embolisms (ischemic stroke, IS). In developed countries, it is the third most common cause of death in the adult population. Stroke in children is a rare disorder with a reported frequency of about 3 cases per 100,000 children per year. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…A total of 241 abstracts were retrieved initially. After exclusion of 219 irrelevant or duplicated reports, 22 potentially eligible studies were assessed by reviewing the full text 15 18 , 38 55 . In all, 15 studies were further excluded, including 4 studies with irrelevant outcomes, 3 studies containing ischemic stroke patients, 6 studies in which there was a lack of usable data and 2 prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 241 abstracts were retrieved initially. After exclusion of 219 irrelevant or duplicated reports, 22 potentially eligible studies were assessed by reviewing the full text 15 18 , 38 55 . In all, 15 studies were further excluded, including 4 studies with irrelevant outcomes, 3 studies containing ischemic stroke patients, 6 studies in which there was a lack of usable data and 2 prospective studies.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that the presence of any type of seizures after stroke (early or late) may depend Due to the heterogeneity of AIS, different sets of genetic and non-genetic risk factors may exist and be related to the etiology and neurological burden of the disease in different populations. Among these factors, thrombophilia, hyperhomocysteinemia, dyslipidemia or MTHFR, FII, or FV gene polymorphisms can be distinguished [12][13][14]. Previous multicenter genetic studies, of 80 children Hemiparesis, seizures and other movement disorders 2 (2.60) 0 (0.00) 0 (0.00) 0 (0.00) 2 (10.00)…”
Section: Discussionmentioning
confidence: 99%
“…Stroke, a sudden loss of brain functions due to disturbance in the cerebral blood supply with symptoms lasting at least 24 h or leading to death, is the second leading cause of death worldwide (Lee et al 2014a;Kopyta et al 2015). It is also defined as a loss of neurological function of vascular origin, in which signs and symptoms may occcur suddenly (within seconds) or rapidly (within hours) (Guo et al 2013).…”
Section: Introductionmentioning
confidence: 99%